Corporate Social Responsibility sebagai Strategi Komunikasi Bisnis Perusahaan - Marselinus Nuba Sabini; Leila Mona Ganiem (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
This study aims to determine the understanding of the mine repellent group PT.ABC communication strategy through the CSR program. Research using qualitative descriptive approach with the constructivist paradigm. Data collection technique used the techniques of interview and literature study. The study design is done with the design of the case study. The results showed PT.ABC has been running various CSR programs that include four areas of activity: community development, education, health and infrastructure improvements. Nevertheless, the rejection of a repellent group remain. Some of the factors, the program is limited to a certain group, employment is still very limited, and the tendency of corporations to be closed to some sensitive issues like IUP, illegal miners and environmental damage. Constraints faced by the corporation less communicate openly with repellent group, the CSR program is also still limited to a few groups, the limited competence of communicating CSR employee-related mines, as well as the personal interests of the group repellent utilizing the mine issue.